By the hand of Mormon : the American scripture that launched a new world religion - Givens, Terryl (UPSO - Oxford University Press E-Books., 2002)
Terryl Givens offers a full-length treatment of the Book of Mormon's history and argues that it is the most religiously influential, hotly contested, and, in the secular press at least, intellectually under-investigated book in America.